2005
DOI: 10.1111/j.1600-0625.2005.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Apaf‐1, a key regulator of apoptosis, in melanoma progression and chemoresistance

Abstract: Apoptosis protease-activating factor-1 (Apaf-1) is a key regulator of the mitochondrial apoptotic pathway, being the central element of the multimeric apoptosome formed by procaspase 9, cytochrome c, and Apaf-1 itself. In this review, the principal aspects about Apaf-1 gene structure and function, and its role in the apoptotic machinery, are described. Moreover, the most recent findings about the involvement of this molecule in melanoma progression and chemoresistance, as well as the clinico-pathological relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…Because most chemotherapeutics function by triggering the apoptotic pathway, apoptotic deregulation in melanoma cells plays an important role in promoting chemoresistance to these agents (4,36,46,47). The identity of PRAS40 as an Akt3 substrate promoting apoptotic deregulation and chemoresistance in melanoma cells is important for unraveling effective therapeutic strategies for melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because most chemotherapeutics function by triggering the apoptotic pathway, apoptotic deregulation in melanoma cells plays an important role in promoting chemoresistance to these agents (4,36,46,47). The identity of PRAS40 as an Akt3 substrate promoting apoptotic deregulation and chemoresistance in melanoma cells is important for unraveling effective therapeutic strategies for melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the gene array study, we found ApaF1 was elevated in the tumors in the WT mice compared to HFE mutant mice. APAF1 is a known regulator of apoptosis in cancers, including melanoma [26]. However, melanomas typically show downregulation of APAF1, so the lower APAF1 levels seen in H67D organisms, which possessed smaller tumors, was counterintuitive [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Mature caspase-9 triggers a caspase cascade, necessary for apoptosis (29,30). APAF-1 was identified as a potential cellular target of FUS1, which is a novel tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%